A166 ABDOMINAL TUBERCULOSIS COMPLICATED BY GASTROINTESTINAL PERFORATION: A CASE REPORT. (15th March 2019) - Taylor, S A; Cygler, J; Kortan, P
Abstract: Background: Abdominal tuberculosis is a rare disease in North America, and the nonspecific presentation poses diagnostic and treatment challenges. A high degree of clinical suspicion is required to make the diagnosis. Abdominal TB in itself has several different manifestations and can present as intra-abdominal lymphadenopathy, peritoneal TB, gastrointestinal tract TB, or solid organ TB (primarily liver and spleen). We present the case of a renal transplant patient with an ileal perforation while on anti-TB treatment for ileo-cecal TB. Aims: Abdominal tuberculosis should be considered in the differential diagnosis during the histopathologic evaluation in immunocompromised patients such as renal transplant recipients. Methods: Case report and literature review. Results: A 62-year-old Pilipino female with a history of end stage renal disease and a remote renal transplant was referred to our emergency department for significant unintentional weight loss of (57 kg deficit from baseline) and cyclical febrile illness. Medications included tacrolimus and mycophenolate. Physical examination demonstrated profound cachexia with a body mass index (BMI) of 16.5 and mild right upper quadrant tenderness. Initial laboratory and infectious workup was non-contributory. Abdominal computed tomography (CT) demonstrated a soft tissue mass at the porta hepatis region and diffuse lymphadenopathy and thickening of the terminal ileum. Colonoscopy established multiple aphthous ulcers, a patulous ileo-cecal valve, necrotic tissue in the terminal ileum and a small fistulous tract in the cecum with a clear patent opening. Biopsies were taken, which revealed small-intestinal type mucosa with reactive changes, focal erosions, underlying lympho-histiocytic infiltrate without granulomas, as well as a positive Ziehl-Neelsen stain for acid-fast bacilli. Based on these findings, the final diagnosis of intestinal tuberculous was made and antitubercular therapy was initiated. A week later, she developed drowsiness, progressive abdominal tenderness, and hypotension. A subsequent CT scan demonstrated mesenteric stranding, increasing ascites and pneumoperitoneum. Emergent laparotomy confirmed a 1.5 cm perforation proximal to the ileocecal valve. Disseminated plaques on the peritoneum as well as on the gallbladder were felt to be in keeping with abdominal tuberculosis. Despite continued anti-tubercular therapy the patient passed away secondary to multiorgan failure. Conclusions: This case highlights intestinal perforation as a serious and rare complication of abdominal tuberculosis which can occur even during TB treatment. In this case, a possible paradoxical reaction to TB treatment, a co-inciding C difficile infection, immunosuppression and poor nutritional status may have contributed to the intestinal perforation. Funding Agencies: CAG